Violência doméstica e educação: um estudo sobre a aplicabilidade da Lei Municipal Marielle Franco (13.566/18) na rede municipal de ensino de João Pessoa-PB - Marrocos, Maria Sandra Pereira (2022)
The present dissertation is a study on the applicability of the Marielle Franco Municipal Law (13.566/18) in the municipal education network of João Pessoa - PB, presented with the Postgraduate Program in Social Service - PPGSS, of the Federal University of Paraíba - UFPB . Methodologically, it is an exploratory field research, with a qualitative approach, having as locus 9 schools of the municipal education network in the city of João Pessoa - PB, divided into 5 Poles, and chosen at random, the subjects of the The research is composed of the Secretary of Public Policies for women in the city of João Pessoa, Mrs. Nena Martins, and 17 teachers, most of them female, brown, aged between 33 and 58 years. The research took place from June 2021 to June 2022, through semi-structured interviews and unsystematic observation, in which we analyzed from the critical dialectical method, whose results showed that of the 09 schools investigated, 67% of them know the Municipal Law nº 13,566 /2018 – Marielle Franco Law and 33% do not know. As for applicability, of these 56% apply, 33% do not apply and 11% partially apply the Law. 59% of respondents know the Law and 41% do not know, of the 10 who claim to know, 70% consider that the Marielle Franco Law contributes to the prevention and fight against domestic violence, 20% did not respond and 10% consider that it contributes partially, of these 70 % have heard of the Marielle Franco Law (nº 13.566/18), but only 41% actually know about it and, unfortunately, the majority, 59%, do not know it. Therefore, we assess that although this law is already present and is applied in some schools of the municipal education network of João Pessoa-PB, it still needs to be better disseminated and developed as it is regulated. However, even schools that do not apply it, somehow have worked on the issue of domestic violence in their spaces, which ends up being relevant to be recorded in this study.